A waterborne polyurethane coating functionalized by isobornyl with enhanced antibacterial adhesion and hydrophobic property. (November 2018) - Wu, Jianhui; Wang, Chunhua; Mu, Changdao; Lin, Wei
Graphical abstract: Highlights: Isobornyl groups can be successfully incorporated into PU by thiol-ene reaction and poly-addition. Introduction of isobornyl groups into PU markedly increases anti-bacterial adhesion performance. The hydrophobicity of the coating films are significantly improved as a result. Abstract: We report a novel environmental friendly waterborne polyurethane (WPU) coating with good anti-bacterial adhesion property and hydrophobicity. A key point of our approach is to functionize the polyurethane with isobornyl acrylate (IBA), a widely used natural material with unique chiral feature and good biocompatibility. The polyurethanes containing IBA have been synthesized by thiol-ene Michael addition reaction and poly-addition polymerization. The thiol monomer 3-mercapto-1, 2-propanediol (TPG) and vinyl monomer isobornyl acrylate (IBA) have been used to obtain dihydroxy-terminated IBA (IBA(OH)2 ) with triethylamine as catalyst. The structure of IBA(OH)2 have been identified by Fourier transform infrared spectrum (FTIR), proton nuclear magnetic resonance ( 1 H NMR), and mass spectrometry (MS). IBA(OH)2 is then incorporated into polyurethane as a chain extender to yield a WPU with IBA side group (IWPU). The synthesized IWPU has been confirmed by FTIR, 1 H NMR, X-ray photoelectron spectroscopy (XPS), and gel permeation chromatography (GPC). Thermogravimetric Analysis (TGA) measurements indicate that the thermal stability of IWPU is decreased slightly with the increasing content of IBA(OH)2 . Differential scanning calorimetry further (DSC) indicate that the T g of the IWPU coatings decreases, and the resistance to low temperature increases at a higher content of IBA(OH)2 .The introduction of IBA side groups can improve the hydrophobicity of the polyurethane, which is favorable for wide application of the coatings. Additionally, the antibacterial adhesion performance of the polyurethanes has been evaluated by plate count method and optical density ( OD ) test. The results demonstrate that the polyurethane coatings with 25 wt% content of IBA side groups can exhibit effective resistance to bacterial adhesion, with the inhibition ratios of 89.3% and 80.4% for E. coli and S. aureus, respectively.